2006
DOI: 10.1557/proc-0965-s03-04
|View full text |Cite
|
Sign up to set email alerts
|

Improved Stability of Solid State Light Emitting Electrochemical Cells Consisting of Ruthenium and Iridium Complexes

Abstract: Two charged organometallic complexes containing bulky hydrophobic ligands based on ruthenium (II) and iridium (III) were synthesized and their performance in solid state light emitting electrochemical cells is described. The complexes were chosen as due to their large ligands a diminished susceptibility towards the formation of destructive complexes during device operation is expected. The LEC device performances reveal the longest living devices reported so far under dc bias. Quantum chemical calculations con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In 2006-2007, a large number of heteroleptic iridium(III) complexes bearing two cyclometalated phenylpyridines and an ancillary diimine ligand such as bipyridine [64][65] or phenanthroline [66][67][68] were reported to act as emitters in electroluminescent devices. DFT calculations on this family of phosphorescent iridium(III) compounds showed that the HOMO is mostly an antibonding combination of Ir (t 2g ) orbitals and π orbitals of the cyclometalated ligand whereas the LUMO is localized on the π* antibonding orbitals of the ancillary ligand [64][65][66][67][68].…”
Section: Cationic Bis-cyclometalated Phenylpyridine Iridium(iii) Complexes With Diimine or Aryl Isocyanide Ancillary Ligandsmentioning
confidence: 99%
“…In 2006-2007, a large number of heteroleptic iridium(III) complexes bearing two cyclometalated phenylpyridines and an ancillary diimine ligand such as bipyridine [64][65] or phenanthroline [66][67][68] were reported to act as emitters in electroluminescent devices. DFT calculations on this family of phosphorescent iridium(III) compounds showed that the HOMO is mostly an antibonding combination of Ir (t 2g ) orbitals and π orbitals of the cyclometalated ligand whereas the LUMO is localized on the π* antibonding orbitals of the ancillary ligand [64][65][66][67][68].…”
Section: Cationic Bis-cyclometalated Phenylpyridine Iridium(iii) Complexes With Diimine or Aryl Isocyanide Ancillary Ligandsmentioning
confidence: 99%